Kinetics Analysis of Overhead Standing Smash in Badminton - Rusdiana, Agus; Subarjah, Herman; B, Badruzaman; Budiman, Didin; Wibowo, Ricky; Nurjaya, Dede Rohmat; Pramutadi, Asril; Mustari, Andi; Kusdinar, Yopi; Syahid, Angga (Universitas Pendidikan Indonesia, 2021)
The purpose of this study was to analyze the joint motion kinetics of the shoulders, elbows, and wrists between experienced player (skilled player) group and unskilled player group when performing overhead standing smash in badminton game. The samples involved were 26 samples. The samples included 13 male badminton players joining Student Activity Unit who had achieved many achievements and had a high skill (skilled), while the other 13 samples were unskilled players, involving students who had just studied under one year. The mean of participants’ age was 19.4 ± 1.6 years, height was 1.73 ± 0.12m, and body weight was 62.8 ± 3.7kg. This study used 3 Panasonic Handycams, a calibration set, 3D Frame DIAZ IV motion analysis software, and a speed radar gun. Normalization of the kinetic motion score of the shoulder, elbow, and wrist joints was calculated using the inverse dynamics method. The t-test was used to determine the significance of motion kinetic difference of the two different groups. The results presented that the shuttlecock speed of the skilled player group, during the overhead standing smash, showed a significant difference. Meanwhile, the joint motion of the inferior shoulder force, shoulder anterior force, shoulder internal rotation torque, shoulder horizontal abduction torque, elbow anterior force, and wrist flexion torque were higher in the skilled players group than the unskilled player group.